2022
DOI: 10.3390/nu14235104
|View full text |Cite
|
Sign up to set email alerts
|

Nongenomic Activities of Vitamin D

Abstract: Vitamin D shows a variety of pleiotropic activities which cannot be fully explained by the stimulation of classic pathway- and vitamin D receptor (VDR)-dependent transcriptional modulation. Thus, existence of rapid and nongenomic responses to vitamin D was suggested. An active form of vitamin D (calcitriol, 1,25(OH)2D3) is an essential regulator of calcium–phosphate homeostasis, and this process is tightly regulated by VDR genomic activity. However, it seems that early in evolution, the production of secostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 205 publications
1
41
0
Order By: Relevance
“…Vitamin D 3 is a pro-hormone, but it was initially categorized as a vitamin, because it can be absorbed from dietary products, mainly oily fish, fish oil, dairy products, meat, eggs and some mushrooms. Nevertheless, the main source of vitamin D 3 in humans is biosynthesis from 7-dehydrocholesterol in the course of photochemical reaction within the human skin [ 28 ].…”
Section: Vitamin D 3 —Biochemical Structure and Me...mentioning
confidence: 99%
“…Vitamin D 3 is a pro-hormone, but it was initially categorized as a vitamin, because it can be absorbed from dietary products, mainly oily fish, fish oil, dairy products, meat, eggs and some mushrooms. Nevertheless, the main source of vitamin D 3 in humans is biosynthesis from 7-dehydrocholesterol in the course of photochemical reaction within the human skin [ 28 ].…”
Section: Vitamin D 3 —Biochemical Structure and Me...mentioning
confidence: 99%
“…Our suggestion is not that one replaces the other, but that there may be some similarities in function. Furthermore, our intention in this review article was to provide a survey of multiple areas of clinical concern related to how melatonin and vitamin D may be involved in foundational mechanisms associated with a broad spectrum of disease pathologies, including their (1) anti-inflammatory activities [ 15 ]; (2) antioxidant potential [ 16 ]; and (3) mitochondrial regulation [ 17 ].…”
mentioning
confidence: 99%
“…2 The mechanism requires the vitamin D-induced upregulation of genes involved in antioxidant response through vitamin D receptor-mediated genomic pathways with additional activation of nuclear-factorerythroid 2-related factor 2 (Nrf2). 3 Vitamin D3 also has an indirect impact on mitochondria function; indeed, transcriptomic analyses focused on mitochondrial genes showed that vitamin D3 inhibits the expression of several genes involved in oxidative processes and upregulates genes involved in reactive oxygen species defense by Nrf2. 3 Furthermore, in a study using diabetic rats, vitamin D3 injection resulted in the inhibition of nicotinamide adenine dinucleotide phosphate oxidase synthesis in the aorta.…”
mentioning
confidence: 99%